“What I lack is myself”: The Fluid Text and the Dialogic Subjectivity in Susan Howe’s Debths - Partyka, Jacek (Text Matters: A Journal of Literature, Theory and Culture, 2023)
James Joyce’s neologism “debths” (Finnegans Wake) that Susan Howe elects for the title of her 2017 volume of poetry points to at least three semantic coordinates of “obligation,” “trespass,” and “demise,” never—due to its implied transaction between the sound and the spelling—fully yielding to or being appropriated by any stable signification. In Debths, the end of life, writing, and, perhaps, literature are palpable, if overtly manifested, currents of poetic discourse. In my article, I advance the idea of recognizing this tripartite taxonomy as a variant of what Divya Victor calls “extremity.” Within this context, I demonstrate the emergence of a dialogic, intertextual, and appropriative subjectivity of the poet.